Surveillance and prevalence of gastrointestinal parasite of domestic animals in different abattoirs in Bangladesh (Asian-Australasian Journal of Bioscience and Biotechnology, 2022)
The study was conducted to examine the gastro-intestinal parasite infestation of animal at Gopalganj district in Bangladesh during July 2020 to June 2021. Total collected sample were 151, among them 32 cattle and goat 119. Parasites were collected directly from viscera then preserve for further analysis. Age, sex and species of the examined animals were recorded as far as practicable. Overall prevalence of nematodes, cestodes and trematodes were 62.25%, 9.27% and 50.33% respectively. The prevalence of parasites was variable with Paramphistomum spp. (58.29%), Fasciola spp 62.91%, Moniezia spp. (5.3%), Haemonchus spp. (41.06%), Trichuris spp. (3.31%), Oesophagostomum spp. (10.59%), Strongyloides spp. (2.64%), Trichostrongylus spp. (5.29%), Bunostomum spp. (5.96%), Toxocara spp. (25.17%). Parasitic in male and female exhibited no significant variations (p>0.05) between them. The infection was significantly higher in young than in adult. No significant (p>0.05) variation was observed in infection rates between cattle and goats.Asian Australas. J. Biosci. Biotechnol. 2022, 7 (2), 50-56